Digital Competence in Quebec’s Teacher Education Programs: Toward a Critical Perspective - Marín, Victoria I.; Angulo Mendoza, Gustavo Adolfo (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Digital competence, beyond core content knowledge, is a key skill for many teachers in this day and age, and several frameworks for this have been proposed internationally. In Canada, some provinces and territories are currently implementing rules and guidelines regarding the digital competencies of teachers. However, only Quebec has an actual one that is linked to teachers, with specific dimensions integrating critical knowledge and attitudes. This interpretive study examines Quebec’s teacher reference and digital-competency frameworks by exploring their integration into teacher-education programs. Two qualitative data-collection methods, namely, semi-structured interviews and document analysis, were used in this study. The sample included seven university professors from the education departments at different Quebec universities and 34 descriptions of digital technologies courses in Quebec’s teacher-education programs. The main results indicate that digital competence is included in at least one course in teacher-education programs, and that instrumental elements are prioritized over critical and ethical digital dimensions. The findings also highlight professors’ awareness of the importance of further developing these less prominent dimensions. The challenges associated with this integration are acknowledged, and the need for future research to develop pedagogical strategies that promote the acquisition of these competencies is emphasized.